Al Samātu Al Lughowiyyatu Lil Arobiyyati Fil Ma’had Al Islāmi Dirōsatu Hālati Fi Ma’hadi Al ‘Ashri Bil Indōnῑsiyyā - Hasibuan, Renni; Muhammad Jundi; Zaki Abouelnasr Elbaghdadi (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
This research aims to describe the characteristics of the Arabic language used in Pondok Pesantren Modern Alhasyimiah Darul Ulum Sipaho. The study encompasses five main aspects: fluency in Arabic, the structure of the language employed, the influence of the mother tongue on language usage, literal translation, and proposed solutions. The research methodology employed is a qualitative descriptive approach with data collection through interview and observation. Data is subsequently analyzed using deduction and description methods. The findings of this study reveal that Pondok Pesantren Modern Alhasyimiah Darul Ulum Sipaho places a strong emphasis on fluency in the Arabic language as a crucial aspect of Arabic language proficiency. However, the teaching of language structure is somewhat limited, resulting in various structural errors in everyday Arabic communication. Additionally, the influence of local languages or dialects on Arabic language usage is present, yet a practical approach to Arabic language instruction boosts students' confidence in communication. The phenomenon of literal translation in Arabic also underscores the importance of contextual understanding in foreign language use. As a solution, the pesantren offers supplementary training programs, interaction with native Arabic speakers, and the promotion of active Arabic language use in daily life. The results above imply the importance of emphasizing contextual understanding and active use of the Arabic language in daily life, as well as the need for a practical approach to teaching language structure to enhance everyday communication in Arabic.